Specific Parameters of Intraoperative Changes in the Hemostasis System during Liver Resection in Children - D. I. Novikov; A. Yu. Zaitsev; K. V. Dubrovin; E. K. Bespalov; A. V. Filin (Вестник анестезиологии и реаниматологии)
The objective: to determine severity of changes in the hemostasis system in children occurring at main stages of liver resection as well as the need for their intraoperative correction.Subjects and Methods. A single-center prospective pilot study of coagulogram and rotational thromboelastometry values was conducted in 25 children aged 0–11 years old with hepatoblastoma after a course of chemotherapy according to the PRETEX IV regimen who underwent hemihepatectomy.Results. There were no statistically significant differences in parameters of the ROTEM tests both when comparing groups and when comparing hemihepatectomy stages within the same age group of patients. At the beginning of the separation of the liver parenchyma INTEM: CT 200.00 (186.00; 238.00), CFT 88.00 (83.00; 139.00), MCF 54.00 (51.00; 61.00), ML 0.00 (0.00; 5.00) in Group I, CT 191.00 (179.00; 199.00), CFT 84.00 (79.00; 103.00), MCF 60.00 (58.00; 64.00), 4,00 (3.00; 9.00) in Group II, respectively, p > 0.05. After separation of the liver parenchyma INTEM: CT 201.00 (161.00; 237.50), CFT 93.00 (95.00; 112.00), MCF 54.00 (52.50; 59.50), ML 6.00 (2.00; 10.00) in Group I, CT 229.00 (201.00; 285.00), CFT 93.00 (78.00; 177.00), MCF 59.00 (49.00; 60.00), ML 5.00 (5.00; 10.00) in Group II, respectively, p > 0.05.Conclusion. After chemotherapy courses, children aged 0–11 years suffering from hepatoblastoma, maintain normal functional activity of the hemostasis system at all stages of surgical treatment. In children under 11 years of age, routine hemostasis correction with blood products and prothrombin complex factor concentrate is not required during the main stages of hemihepatectomy.